The Dynamics of Interreligious Marriage in Indonesian Religious and Legal Perspectives - Aldi Subhan Lubis; Zaini Muhawir (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2023)
Mixed marriages due to ethnicity have become commonplace in Indonesia. Still, a wedding occurs due to differences in the faith or religion of the prospective partner. In that case, it will cause new problems related to the legal status of the marriage or the legal consequences arising from the wedding. This type of research is normative juridical research using data from primary, secondary and tertiary legal materials. Based on the research results, it is known that some religions in Indonesia strictly prohibit it, while others forbid it but are still allowed. For example, Islam strictly prohibits marriage to faith outside of Islam. Christianity and Catholicism are also banned because they consider marriage not ideal. If the Hindu religion believes that if it is done outside of Hinduism, then the marriage is deemed invalid, while Buddhism and Confucianism do not have a problem with this. Related to the formal juridical aspect, this interfaith marriage is legal because this interfaith marriage has been recorded and has a marriage certificate issued by an official of the Population and Records Service Office by Article 2 paragraph (2) of the Marriage Law, but only in an administrative form. Meanwhile, this interfaith marriage is invalid if we look at the applicable legal regulations. From the research above, it can be concluded that unions carried out with different religions can only be registered administratively; from a legal and religious point of view, each is considered invalid because there are no clear rules governing it.